EVALUATION OF PATIENT’S AWARENESS REGARDING PATIENT RIGHTS: A CROSS-SECTIONAL STUDY - LATIF , Z; NAYAB , S (Biological and Clinical Sciences Research Journal, 2024)
Understanding and respecting patient rights are critical to healthcare quality and safety. However, there is limited data on the level of awareness among patients in Pakistan, particularly in public hospitals. Objective: This study aimed to evaluate the awareness of patients’ rights among individuals visiting the inpatient departments of Nishtar Hospital, Multan, and Aziz Bhatti Teaching Hospital, Gujrat. Methods: A cross-sectional study was conducted in the Inpatient Departments of Nishtar Hospital and Aziz Bhatti Teaching Hospital from June 2023 to June 2024. A total of 200 patients were included in the study. Data were collected using a 14-item questionnaire divided into two sections. The first section gathered demographic information, including age, sex, qualification, and residence. The second section assessed awareness of patients’ rights as outlined in the Charter by the Punjab Healthcare Commission, with responses graded on a 4-point Likert scale. Statistical analysis evaluated the association between awareness and demographic variables, with significance set at p<0.001. Results: The mean awareness score among the patients was 23.85 ± 5.05. Good awareness of patients’ rights was observed in 11.5% of patients, while 60.1% had moderate awareness and 28.4% had poor knowledge. The highest score (3.20 ± 1.01) was recorded for awareness of the healthcare staff’s identity and trustworthiness. Conversely, the lowest score (1.76 ± 0.72) was associated with awareness of the right to be consulted about treatment options and potential complications. A significant association was found between total awareness scores and various charter sections (p<0.001). Additionally, residence and educational qualification were significantly associated with awareness levels, with urban residents and more educated patients demonstrating higher awareness (p<0.001). Conclusion: The study found a moderate level of awareness of patient rights among individuals visiting the inpatient departments of the studied hospitals. These findings underscore the need for healthcare reforms and targeted awareness programs to improve patients’ knowledge of their rights, thereby enhancing overall healthcare quality and patient satisfaction.